2021
DOI: 10.22201/ib.20078706e.2021.92.3795
|View full text |Cite
|
Sign up to set email alerts
|

Variación del estadio embrionario de Basiliscus vittatus (Squamata: Corytophanidae) en la oviposición

Abstract: ResumenEn lagartijas ovíparas existe un intervalo frecuente en el desarrollo embrionario que alcanzan los huevos al momento de la oviposición entre el estadio 26 y 33. Dicha variación se ha relacionado con el origen de la viviparidad y permite la exploración de los efectos experimentales en el desarrollo embrionario después de la oviposición. Sin embargo, para la mayoría de las especies de lagartijas, el estadio embrionario en la oviposición es desconocido. El presente estudio detalla por primera vez en Coryto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Forty-two eggs (32%) became contaminated with fungal infection and the embryos died with no correlation with the incubation temperature ( X 2 test, P > 0.05). Of the 88 eggs that successfully reached the target developmental stages, 40 were used in a parallel study that aimed to establish the effect of incubation temperatures on the development of the embryos [ 27 ]. Finally, forty-eight eggs (12, 18, 18 for 26°C, 29°C, and 32°C, respectively) reached the target stages 35–37.…”
Section: Methodsmentioning
confidence: 99%
“…Forty-two eggs (32%) became contaminated with fungal infection and the embryos died with no correlation with the incubation temperature ( X 2 test, P > 0.05). Of the 88 eggs that successfully reached the target developmental stages, 40 were used in a parallel study that aimed to establish the effect of incubation temperatures on the development of the embryos [ 27 ]. Finally, forty-eight eggs (12, 18, 18 for 26°C, 29°C, and 32°C, respectively) reached the target stages 35–37.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, the only data available regarding the reproductive biology of B. vittatus are in the female's average size of the clutch and the rate of embryonic development at oviposition (Suárez‐Varón et al, 2019; Suárez‐Varón et al, 2021), and a more recent study that demonstrated the lack of temperature sex determination in this species (Suárez‐Varón et al, 2022). Based on this limited reproductive data, the goal of this study is to explore male reproductive morphology within this species throughout the reproductive cycle.…”
Section: Introductionmentioning
confidence: 99%